1947
DOI: 10.1021/ja01198a513
|View full text |Cite
|
Sign up to set email alerts
|

A Synthesis of Nordihydroguaiaretic Acid

Abstract: NotesVol. 69 hydrate. This crude material contained 96% of the theoretical electropositive chlorine content. When it was distilled at 76-78°(10 mm.) this chlorine content was found to be 99% of theoretical. The distilled product melted at 4-4.5°cor., á204 1.544. Since the crude material is sufficiently pure for most purposes, the distillation, which is dangerous, ought to be avoided. z-Propyldichloramine was prepared by a modification of the above procedures. To an ice-cooled concentrated aqueous solution of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1949
1949
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…NDGA has also been synthesized by Lieberman, Mueller, and Stiller (204), who have patented their process (231). Their process involves the following I«]d = 0° (272) NDGA (from creosote bush).........................…”
Section: Nordihydroguaiaretic Acidmentioning
confidence: 99%
“…NDGA has also been synthesized by Lieberman, Mueller, and Stiller (204), who have patented their process (231). Their process involves the following I«]d = 0° (272) NDGA (from creosote bush).........................…”
Section: Nordihydroguaiaretic Acidmentioning
confidence: 99%
“…Hwu reported that NDGA and its analogues exhibited activity against HIV, and tetramethyl NDGA was a stronger anti-HIV agent. 17 Son et al developed a modified procedure for the synthesis of NDGA and related lignans. 13 NDGA, (-)-saururenin and their analogues have also been shown to have cancer chemopreventive properties.…”
Section: Introductionmentioning
confidence: 99%
“…HCI (10%) to remove the pyridine. The standard ethereal workup followed by purification by FCG afforded the desired product 8 as a white solid (1.2 g, 95%): mp 78-80°C; mlz (ElMS) 318, 316 (M+), 276, 237 (6) Isopregomisin I.-To the Grignard reagent made from magnesium turnings (72 mg, 3 mmol) and compound 8 (640mg, 2 mmol) in dry THF (10 ml) was added dropwise a solution of (E)-2-tert-butyl-3- Our synthetic strategy (outlined in Scheme I) started from pyrogallol 2, which was easily converted into trimethyl pyrogallol 3. Treatment of 3 with ZnCl 2/propionic acid gave 2,6-dimethoxyphenol (4) in a yield of 71%.…”
mentioning
confidence: 99%